Notes on the plants of Bakossi, Cameroon, and the new Cola etugei and Cola kodminensis (Sterculiaceae s. str.) - Martin Cheek; Barthelemy Tchiengue; Isabel Baldwin (Plant Ecology and Evolution, 2020)
Background and aims – This paper reports a further discovery during preparation for a monograph of the genus Cola, and also in the context of a long-term botanical survey in the Cross River-Sanaga interval of west-central Africa, focussing on species discovery and conservation through the Tropical Important Plant Areas programme.Methods – Normal practices of herbarium taxonomy have been applied to study the material collected. The relevant collections are stored in the Herbarium of the Royal Botanic Gardens, Kew, London (K) and at the Institute of Research in Agronomic Development – National Herbarium of Cameroon (YA). Key results – Two species new to science, small trees or shrubs of cloud forest, are formally named from the Bakossi tribal area and assessed for their conservation status. Cola etugei, is endemic to the western slopes of Mt Kupe with conservation status assessed as Critically Endangered (CR B1+2ab(iii)) according to the 2012 criteria of IUCN. Cola kodminensis from the Bakossi Mts is also assessed as Critically Endangered (CR B1+2ab(iii)). This publication increases the number of documented narrowly endemic, threatened species in the Bakossi tribal area, and helps make the case for formal protection of Mt Kupe, which with 33 endemic and near-endemic plant species remains an extremely high candidate for such protection. Further effort is needed to publish the remaining informally named species of this location, and investment to support the protection of the mountain by local communities.